The Effect of pH-regulated EDTA on Root Canal Dentin - Ryuji, FUJIMAKI; Jiro, SUZUKI; Nobuyuki, TANI-ISHII (The Japanese Journal of Conservative Dentistry, 2020)
Purpose: The purpose of this study was to evaluate the dentin demineralization and smear layer removal ability of 3% EDTA of pH 12.2 (pH 12.2 EDTA) as a root canal irrigant. Method: The demineralization effect of the pH 12.2 EDTA was analyzed using 10 human permanent teeth with a single root canal. The test samples were prepared by inducing a smear layer on the cross section of dentin after vertically cutting the teeth, and 3% EDTA of pH 9.0 was used as a control group. The pH 12.2 EDTA was used to irrigate the test samples for 1 to 60 minutes, and the surface hardness of the root canal dentin at each working time was measured by the indentation hardness test (HIT) and the indentation elastic modulus test (EIT). The effect of removing the smear layer was determined by observing the dentin surface by SEM after the pH 12.2 EDTA was applied for each irrigation time, and the state of the remaining smear layer was determined by the 5-step method according to the method of Hülsmann. Regarding the chemical stability analysis, the pH 12.2 EDTA solution was classified into storage groups at 25°C and 40°C, and the pH changes and changes of EDTA content were analyzed after storage for 6 months. Results: No statistically significant differences of dentin demineralization were found by measuring HIT and EIT. The residual smear layer in the test samples was not observed, and there was no significant difference compared with the pH 9.0 EDTA control group. Furthermore, no significant difference was found in change in dentin hardness after irrigation and the removing effect of the smear layer in the coronal, middle and apical of the root canal. Furthermore, no change was observed in color tone or properties for 6 months under the conditions of storage at 25°C and 40°C. Conclusion: The pH 12.2 EDTA solution was shown to have excellent smear layer removal effect and chemical stability as a root canal irrigant.